WHEAT(TRITICUM AESTIVUM TRITICUM AESTIVUM TRITICUM AESTIVUM L.) CULTIVAR PERFORMANCE AND STABILITY AMONG VARIOUS TILLAGE METHODS IN WESTERN UTTAR PRADESH CONDITION - ASHISH DWIVEDI2, PARDEEP KUMAR1 *, R. K. NARESH2; VINOD KUMAR, ROBIN KUMAR1 , SIKHA GANGWAR1; AND ANUJ KUMAR (The Bioscan, 2016)
A 2-year field study was conducted to evaluate the wheat cultivar performance and stability among various tillage methods. 7 tillage crop establishment methods (T1 -Zero till without residue, T2 -Zero till with residue, T3 -Wide raised beds without residue, T4 -Wide raised beds with residue, T5 -Narrow raised beds without residue, T6 - Narrow raised beds with residue T7 , Conventional tillage)in main plot and 10 wheat varieties treatments (V1-UP 2338, V2 -WH 542,V3 -PBW 154,V4 -DBW 17,V5 -WH 711,V6 -HD2687,V7 -PBW 343,V8 –UP2382,V9 -HD1731,V10 -PBW 502) in sub plots were tested in SPD by using F test. The experimental findings revealed that T6 measured maximum average plant height (92.15 cm), dry matter accumulation (141.5 g) and number of tillers (108/mrl). Moreover, T4 were also noticed significantly higher yield attributes and yield viz., number of grains per spike, spike length, numbers of spikelets per spike and test weight. Whereas, the improvement in average grain yield 11.3/10.9% due to residue retention on wide raised beds/narrow raised beds, respectively over T7 during both the year. Likewise, DBW 17 noticed maximum growth; yield attributes and yields than rest of its counterparts. The study suggested